An image-based method to measure joint deformity in inflammatory arthritis: development and pilot study. Issue 10 (27th July 2019) - Henchie, Travis F.; Gravallese, Ellen M.; Bredbenner, Todd L.; Troy, Karen L.
Abstract: Quantifying joint deformity in people with rheumatoid (RA) and psoriatic arthritis (PsA) remains challenging. Here, we demonstrate a new method to measure bone erosions and abnormal periosteal growths, based on the difference between a predicted healthy and actual diseased joint surface. We optimized the method by creating and measuring artificial bone erosions and growths. Then we measured 46 healthy and diseased patient surfaces. We found average sensitivity errors of ≤0.27 mm when measuring artificial erosions and growths. Patients had significantly more bone erosion than healthy subjects. Surface based outcomes are a novel way to interpret and quantify bone changes in PsA and RA.